Teachers' Views on the Use of ICT in Language Courses - Harmita Sari; Rahmat Kamaruddin; Anshari, Anshari; Andi Nurhayati; Samsinar, Samsinar (Universitas Cokroaminoto Palopo, 2025)
This study aims to explore and understand teachers' perceptions regarding the integration of Information and Communication Technology (ICT) in English for Specific Purposes (ESP) instruction, with the goal of identifying both benefits and challenges in real classroom settings. A qualitative case study design was employed to gain in-depth insights into the phenomenon. Data were collected through semi-structured interviews with two experienced language instructors from a private university in South Sulawesi, Indonesia. The interviews were transcribed and analyzed thematically using Nvivo R14 software to ensure systematic coding and theme development. The findings revealed two primary themes: teachers’ positive perceptions and the challenges they face in using ICT. The participants highlighted that ICT tools facilitate ESP teaching by supporting material delivery and increasing student engagement. Nonetheless, they also reported significant challenges, including limited internet connectivity, increased instances of plagiarism, and difficulties in monitoring student performance. This study provides up-to-date insights into the practical realities of ICT integration in ESP instruction within Indonesian higher education, offering valuable implications for educators, policymakers, and curriculum developers aiming to optimize ICT use in language teaching.